Cash economy: tax evasion among SMEs in Malaysia - Mohamad, Azhar; Zakaria, Mohd Hasrol; Hamid, Zarinah (Emerald Group Publishing Ltd., 2016)
Purpose – The purpose of this study is to investigate the relationship between tax evasion and certain demographic factors such as location, engagement of tax agent, size and type of small- and medium-sized enterprises (SMEs) industry in Malaysia. Design/methodology/approach – In this study, using proprietary tax audit data from the Inland Revenue Board of Malaysia (IRBM) on the 2011 tax returns of SMEs, the authors run a multiple regression analysis to examine the impact of location, agent, type of industry, size of enterprise and type of tax evasion on SMEs’ tax evasion in Malaysia. Findings – The authors find that tax evasion among SMEs in Malaysia is the highest when the business is located in a suburban environment and has no tax agent. Tax evasion is also influenced by the size of the SME (micro or medium). Originality/value – This study gives insight that the IRBM can use to aid its collection department in profiling SMEs that have a higher tendency to evade paying tax. Keywords Malaysia, SMEs, Tax evasion, Cash economy, Corporate income tax